Cu2O-loaded heteroatom-doped worm-like hierarchical porous carbon flakes for high-performance energy storage devices. (8th June 2021) - Wu, Fuming; Gao, Jianping; Zuo, Saisai; Wang, Wei; Qiu, Haixia
Highlights: Cu2 O-loaded S-doped hierarchical porous carbon flakes (SCu-HPCFs) were successfully prepared. Heteroatom-doped hierarchical porous carbon flakes exhibit high specific surface area. The specific capacitance of SCu-HPCFs can reach 451 F g −1 at 1 A g −1 . The asymmetric supercapacitor exhibited super-long cycle life and high energy density. Abstract: In this paper, Cu2 O-loaded S-doped worm-like hierarchical porous carbon flakes (SCu-HPCFs) have been prepared for supercapacitor applications by using cheap sweet potato starch as a raw material via a controlled carbonization–activation-hydrothermal reaction process. The as-prepared SCu-HPCFs possess hierarchical porous structure, large specific surface area (2543.68 m 2 g −1 ), s doping state and good electrical conductivity. The SCu-HPCFs electrode exhibits a high specific capacitance of 451 F g −1 at 1 A g −1 and good rate capability (retention of 79% from 1 to 15 A g −1 ). Moreover, the asymmetric supercapacitor assembled using the SCu-HPCFs as a negative electrode and NiO/RGO as a positive electrode shows a high energy density of 30.2 W h kg −1 at a high power density of 800.4 W kg −1 and can still achieve 23.5 W h kg −1 at 8070.9 W kg −1 . At the same time, it has excellent cycling stability (90.8% retention after 10, 000 cycles). The high capacity performance can be attributed to rich porous structure, high specific area and pore volume, Faraday contribution caused by S doping and the fast redox reaction of Cu2 O.